Cognitive performance among participants with Alzheimer's disease and cerebral amyloid angiopathy: Neuropsychology/Neuropsychological correlates of physiologic markers of cognitive decline/Dementia. (7th December 2020) - Teylan, Merilee; Schwabe‐Fry, Kristen; Hughes, Timothy M.; Besser, Lilah M; Brenowitz, Willa D.; Keene, C. Dirk; Gauthreaux, Kathryn; Culhane, Jessica E.; Miller, Zachary; Chen, Yen‐Chi; Chan, Kwun Chuen Gary; Mock, Charles; et al.
Abstract: Background: Beta‐amyloid found in Alzheimer's disease (AD) plaques can also be present in the brain's blood vessels as cerebral amyloid angiopathy (CAA). Co‐occurrence of AD and CAA is common. We examined the relationship between AD and CAA, and cognitive performance. Method: Data were obtained from the National Alzheimer's Coordinating Center. The sample was restricted to those with an autopsy ≤2 years of their last clinic visit and non‐missing data on Braak neurofibrillary tangle stage, neuritic plaque score, and CAA at autopsy. We excluded participants who had autopsy evidence of rare neuropathological diseases. Linear regression models with generalized estimating equations were run comparing CDR ® Dementia Staging Instrument sum of boxes (CDR‐SB) and cognitive domain z‐scores across four groups (AD+/CAA+, AD+/CAA‐, AD‐/CAA+, AD‐/CAA‐). AD+ included those with Braak III‐VI and moderate/frequent neuritic plaques. Overall neocortical amyloid angiopathy was assessed for presence of CAA. Models accounted for clustering by center and adjusted for covariates. We also examined the mean differences in CDR‐SB by CAA severity (absent, mild, moderate, severe), stratifying by AD+/‐ and APOE ε4+/‐. Result: We identified 1723 AD+/CAA+, 547 AD+/CAA‐, 443 AD‐/CAA+, and 741 AD‐/CAA‐ participants. All groups were more likely to be APOE ε4 carriers compared to AD‐/CAA‐. CAA+ participants, regardless if they had AD, were more likely to have arteriolosclerosis. After adjusting for covariates, AD+/CAA+ and AD+/CAA‐ participants had worse CDR‐SB scores compared to AD‐/CAA‐. There was no significant difference in CDR‐SB scores among AD‐ participants with or without CAA. Similar results were seen when examining differences in cognitive domain z‐scores, where AD+ participants performed worse regardless of the presences of CAA when compared to AD‐/CAA‐ participants. We did not observe significant differences in CDR‐SB scores by CAA severity after adjusting for covariates. Conclusion: These results demonstrate that the presence of AD neuropathologic features appears to be driving the cognitive performance irrespective of the presence or severity of CAA. Our observation that arteriolosclerosis was more likely to be present among those with CAA even in the absence of AD is of note and something to investigate further. Future work should also examine if these differences hold true when examining longitudinal cognitive performance.